2021
DOI: 10.1109/tsg.2021.3091535
|View full text |Cite
|
Sign up to set email alerts
|

A Cyber Attack Mitigation Scheme for Series Compensated DFIG-Based Wind Parks

Abstract: Subsynchronous Interaction (SSI) phenomenon is known to be one of the most frequent and severe stability issues of a Wind Park (WP), and can potentially lead to a significant loss of power generation. The broad impacts of this phenomenon on a power grid have made WPs interesting targets for cyber attacks. To initiate the SSI, an adversary can target either the power grid (external attacks) or the cyber system of WPs (internal attacks). This paper proposes a mitigation scheme for attacks that initiate the SSI p… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 20 publications
(2 citation statements)
references
References 45 publications
0
2
0
Order By: Relevance
“…If cyber security is not managed and controlled effectively, the cyber-attack can reduce the stability of the operation network as evidenced by the U.K. power outage in 2019 [43] and the ERCOT incident in 2009 [44]. In March 2019, a cyber-attack targeted a wind plant in Salt Lake City, Utah, U.S., resulting in the loss of operator control over wind turbines [45]. Subsequently, The U.S. Department of Energy emphasized the critical necessity for dedicated efforts to identify vulnerabilities, raise awareness, and develop strategies to protect wind energy infrastructure against cyber-attacks [46].…”
Section: Uncertainties Affecting the Communication Linkmentioning
confidence: 99%
“…If cyber security is not managed and controlled effectively, the cyber-attack can reduce the stability of the operation network as evidenced by the U.K. power outage in 2019 [43] and the ERCOT incident in 2009 [44]. In March 2019, a cyber-attack targeted a wind plant in Salt Lake City, Utah, U.S., resulting in the loss of operator control over wind turbines [45]. Subsequently, The U.S. Department of Energy emphasized the critical necessity for dedicated efforts to identify vulnerabilities, raise awareness, and develop strategies to protect wind energy infrastructure against cyber-attacks [46].…”
Section: Uncertainties Affecting the Communication Linkmentioning
confidence: 99%
“…Series compensation technology is frequently utilized in transmission systems to enhance transmission capacity costefficiently. However, recent research has shown that using series compensation can lead to oscillations in wind turbine generator systems [3], [4], [5]. In fact, in 2009, a wind farm based on a doubly-fed induction generator (DFIG) connected to the grid via a series compensation line experienced a large-scale wind power oscillation in South Texas, causing equipment damage.…”
Section: Introductionmentioning
confidence: 99%